2007
DOI: 10.1111/j.1744-1617.2007.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Child‐focused and Child‐inclusive Divorce Mediation: Comparative Outcomes From a Prospective Study of Postseparation Adjustment

Abstract: This study compared outcomes over 1 year for two groups of separated parents, who attended two different forms of brief therapeutic mediation for entrenched parenting disputes. The two interventions each targeted psychological resolution of parental conflict, enhanced parental reflective function, and associated reduction of distress for their children. The child-focused (CF) intervention actively supported parents to consider the needs of their children, but without any direct involvement of the children, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 23 publications
1
69
0
9
Order By: Relevance
“…Both family mediation and Collaborative Practice utilise child inclusive practice. This has been influenced by empirical and clinical evidence that shows how child inclusive practice centralises the needs of the child by enhancing parents' understanding of their children's experiences, needs and views, and how this leads to more informed and durable agreements that can also influence improved family relationships (McIntosh et al, 2008).…”
Section: Centralising Children's Needs In Family Dispute Resolutionmentioning
confidence: 99%
“…Both family mediation and Collaborative Practice utilise child inclusive practice. This has been influenced by empirical and clinical evidence that shows how child inclusive practice centralises the needs of the child by enhancing parents' understanding of their children's experiences, needs and views, and how this leads to more informed and durable agreements that can also influence improved family relationships (McIntosh et al, 2008).…”
Section: Centralising Children's Needs In Family Dispute Resolutionmentioning
confidence: 99%
“…Estos programas generalmente son breves y didácticos, focalizándose en cómo ayudar a los niños a enfrentar la situación durante e inmediatamente después del proceso de divorcio. Un grupo de investigación en Australia 45 ha implementado un programa de mediación que incluye a los niños y se ha visto que tiene un efecto en reducir los niveles de conflicto y un mejor manejo de éstos. También se proponen nuevos diseños para aplicar en los tribunales con el fin de realizar un divorcio colaborativo en vez un enfoque confrontacional 46 .…”
Section: Rol Del Pediatra En Casos De Divorcio O Separaciónunclassified
“…First, research about children's competencies and rights revealed children's desire to be included in the process (Campbell, 2004;Graham & Fitzgerald, 2010a;James & Prout, 1997;Mayall, 1994;McIntosh, 2003;McIntosh, Well & Long, 2007;Parkinson & Cash-more, 2008;Smart, Neale & Wade, 2001;Smith, Taylor, & Tapp, 2003;United Nations, 1989). Second, researchers found that children and adults who participated in a process that involved children, thought it was potentially beneficial to them (Fitzgerald & Graham, 2011a;Goldson, 2006;Lodge & Alexander, 2010;McIntosh, 2000McIntosh, , 2003McIntosh, Wells, Smyth, & Long, 2008;Moloney & McIntosh, 2004). This led to an acceptance in Australia that what is required is not merely an interest in 'listening to the voice of the child' but listening to the voice of the child because they have the 'right to be listened to'.…”
Section: Introductionmentioning
confidence: 99%